2010
DOI: 10.1099/mic.0.039735-0
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization and expression analysis of a suite of cytochrome P450 enzymes implicated in insect hydrocarbon degradation in the entomopathogenic fungus Beauveria bassiana

Abstract: The insect epicuticle or waxy layer comprises a heterogeneous mixture of lipids that include abundant levels of long-chain alkanes, alkenes, wax esters and fatty acids. This structure represents the first barrier against microbial attack and for broad-host-range insect pathogens, such as Beauveria bassiana, it is the initial interface mediating the host-pathogen interaction, since these organisms do not require any specialized mode of entry and infect target hosts via the cuticle. B. bassiana is able to grow o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
82
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 80 publications
(84 citation statements)
references
References 43 publications
1
82
0
1
Order By: Relevance
“…S1). The region surrounding the start codon contained the eukaryotic consensus (G/A)NNATGG sequence, including a purine (A) in position −3, as has been reported for highly expressed genes in Saccharomyces cerevisiae (46) and has also been found in B. bassiana P450 genes (43). Variants of the tripartite signal [5′-TAG... TA(T/A)GT.…”
Section: Molecular Identification and Expression Analyses Of A Benzoqmentioning
confidence: 82%
See 2 more Smart Citations
“…S1). The region surrounding the start codon contained the eukaryotic consensus (G/A)NNATGG sequence, including a purine (A) in position −3, as has been reported for highly expressed genes in Saccharomyces cerevisiae (46) and has also been found in B. bassiana P450 genes (43). Variants of the tripartite signal [5′-TAG... TA(T/A)GT.…”
Section: Molecular Identification and Expression Analyses Of A Benzoqmentioning
confidence: 82%
“…However, entomopathogenic fungi are incapable of lignin degradation, and no information is available regarding the presence and/or function of these enzymes in this group of fungi. However, entomopathogenic fungi are able to assimilate various hydrocarbon and lipid components of the insect cuticle, responding to surface cues on their hosts to initiate programs for infection (41)(42)(43).…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…CYPs also play a part in fungal pathogenicity against insects. The insect cuticle comprises a mixture of lipids, including long-chain alkanes, alkenes, wax esters and fatty acids, and recently the involvement of CYPs in breaking down this barrier was shown for Beauveria bassiana [75]. Eight CYPs from seven different CYP families were associated with metabolism of cuticle lipid.…”
Section: Microbial Cytochromes P450 and The Environmentmentioning
confidence: 99%
“…Candida spp. contain multiple CYP52s with overlapping substrate specificity shown by biochemical and genetic methods [76,77], and it was suggested that the CYPs identified as being induced by cuticle lipids would also show such overlap [75]. Manipulating these activities could increase virulence and has the potential to assist in bio-control of insects using fungal pathogens.…”
Section: Microbial Cytochromes P450 and The Environmentmentioning
confidence: 99%